IMPLEMENTASI KEBIJAKAN RETRIBUSI PELAYANAN PARKIR DI KABUPATEN PAMEKASAN - Syaiful Anam; Soesilo Zauhar; Sarwono . (REFORMASI, 2015)
Abstract : Parking problem is one of challenging problems to any governments, especially the government of the region with crowded and dense urban structure. The government of Pamekasan Regency has coped with this problem through Local Regulation which principally is designed at maximizing the role of local government as public servant to deliver optimum service to the community, to provide law certainty to the management of parking in Pamekasan, to press down the leakage of parking retribution, to increase Local Genuine Income (PAD) and to ensure the income of parking officer. Research type is qualitative. It means that this research produces a description about things associated with research. Qualitative data emphasize more on words than numbers. Descriptive approach is used and can also be defined as a problem solving procedure because it describes the condition of the subject or object of research, either the behavior of individual, group, community organization, and others, in recent time, or the tangible factors or what as should be.